Global Challenges and Economic Feasibility in Achieving 100% Renewable Energy - Abo Dahab, Ahmed; Abo Adma, Maged; Hassan, Hany; Elazab, Rasha (Recent Advances in Electrical & Electronic Engineering, 2025)
This study aims to investigate the global transition towards 100% renewable energy (RE) grids while analyzing associated challenges and economic prospects. The scientific aim of the work is to examine national and regional plans, revealing shared research challenges such as neglect of system stability, reliance on specific RE sources, and limitations on capacity share growth. The subject of the research was to obtain insights into the economic feasibility of this transition, underscored by projections of creating 24.3 million new jobs by 2050 and substantial annual savings in air pollution and environmental costs. This study extends the existing research by analyzing promising examples from countries like Norway and Costa Rica, demonstrating diverse approaches with hydropower playing a pivotal role, while Canada and New Zealand showcase adaptability based on local resources. Addressing key research challenges, from technological uncertainties to socio-economic considerations, the paper emphasizes the need for robust policies and infrastructure development. Despite challenges, the transition promises economic benefits, with estimated annual savings in healthcare and global warming costs. The literature and global examples affirm the technical and financial feasibility of transitioning to 100% RE. In conclusion, this paper contributes to understanding the intricate economic and technological landscape of achieving a sustainable global energy transition.
Keywords: economic feasibility